"Is Old Gold?" the Role of Prior Experience in Exploring the Determinants of Islamic Social Entrepreneurial Intentions: Evidence from Bangladesh. Issue 2 (4th May 2021) - Ashraf, Mohammad Ali
Abstract: The purpose of this paper is to identify the determinants of Islamic social entrepreneurial intentions (ISEI) in the context of Bangladesh. Specifically, how do empathy, moral obligation, self-efficacy and perceived social support influence Islamic social entrepreneurial intentions through the mediation of prior experience of individual? To answer this question, a theoretical framework using the theory of social entrepreneurial intentions provided (TSEI) by Mair and Noboa as its basis was established. Using measurement scales created to assess different aspects of the constructs, a survey instrument was developed to test the various relationships implied by ISEI. Data ( n = 249) were collected following random sampling procedure from a business school at a private university in Bangladesh. Data were analysed using the procedure of structural equation modelling. Findings show that prior experience both directly and indirectly predicts Islamic social entrepreneurial intentions. Entrepreneurial self-efficacy has both the largest impact on intentions as well as on prior experience.